Is nationality a factor affecting serve type, serve speed, and success in professional volleyball league? - Özünlü, N.; Pekyavas, P.; Cerezci, S.; Duygu, D.; Çinar-Medeni, Ö.; Altundag, E.; Akarçesme, C.; Çolakoglu, F. F.; Baltaci, G. (International Journal of Disabilities Sports and Health Sciences, 2021)
In professional volleyball, serving is one of the most important attacking options. A strong and qualified service is important to be successful in the game. There is limited research about comparison of native and foreign volleyball players and also no research was found about Turkish players. The aim of our study was to determine if being a national or a foreign player affects serve speed, serve type and success. Total of 6168 serve shots were included in our study. Four groups were determined as native woman players (n=1836), foreign woman players (n=1036), native man players (n=1886) and foreign man players (n=1410) serve shots. Serve speeds were measured by using Radar Gun (Pocket Radar, Santa Rosa, CA, USA). Serve types and serve efficiencies were recorded during game. There was significant difference between the groups in terms of serve speeds (F=1012.618 p=0.01). Also statistically significant difference was found bet ween four groups for serve types (p=0.01) and serve efficiencies (p=0.028). Our results might be a result of training type used from the beginning of sports life of the volleyball player. When we consider the findings, we think that the speed, type and effectiveness of serves should be evaluated and followed for training and tactical development.